2020
DOI: 10.3390/en13123276
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design, Analysis, and Testing of a 10 kW Fabric-Covered Wind Turbine Blade

Abstract: Reducing the weight of a wind turbine blade is a major issue. Wind turbines have become larger in size to increase power generating efficiency. The blade has also grown in length to take more wind energy. A fabric-based wind turbine blade, introduced by General Electric Co., reduced the blade weight. In this study, a small fabric-covered blade for a 10 kW wind turbine was developed to verify structural ability. The blade was designed on the cross-section using variational asymptotic beam sectional analysis (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Because of its fabric elasticity, the SC model adapts to surrounding flow and exhibits a different airfoil shape due to surface pressure, resulting in larger coefficients. Theoretical analyses of this phenomenon (i.e., change of lift and drag due to surface deformation) qualitatively supporting the findings presented in this paper are reported in references [2], [3], [4], and [5].…”
Section: Comparison Between Hc and Sc Modelssupporting
confidence: 90%
See 2 more Smart Citations
“…Because of its fabric elasticity, the SC model adapts to surrounding flow and exhibits a different airfoil shape due to surface pressure, resulting in larger coefficients. Theoretical analyses of this phenomenon (i.e., change of lift and drag due to surface deformation) qualitatively supporting the findings presented in this paper are reported in references [2], [3], [4], and [5].…”
Section: Comparison Between Hc and Sc Modelssupporting
confidence: 90%
“…Model analyses of this kind qualitatively supporting these findings (i.e., change of lift and drag due to deformation of surface) presented in this paper has also been reported in Refs. [2], [3], [4] and [5].…”
Section: Lift-to-drag Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The research on small wind turbine blades is mainly focused on the development of new airfoils and the determination of the aerodynamic performance of the wind turbine blade and/or rotors [15][16][17][18]. Based on a literature search, it was observed that only a few researchers have attempted the task of static and fatigue strength design of small wind turbine blades [19][20][21][22]. Specifically, the design of airfoil chord length and thickness based on the aerodynamic and strength performance is studied by a few researchers.…”
Section: Introductionmentioning
confidence: 99%
“…A wind turbine blade made of fabric-based material can reduce the blade weight. To verify structural capability, Choi et al [7] developed a 10 kW wind turbine with small fabric-covered turbine blades. They designed the cross section of turbine blades by using Variational Asymptotic Beam Sectional analysis (VABS), then they implemented structural analysis.…”
Section: Introductionmentioning
confidence: 99%